Comparison Of Durability Between Uv Inkjet And Conventional Offset Prints Exposed To Accelerated Ageing - Mirica Karlovits; Diana Gregor-Svetec (Journal of Graphic Engineering and Design, 2011)
The present study deals with the optical and colour stability of aged offset and UV inkjet prints. As a paper substrate,a film synthetic paper was used, which was printed by two techniques (UV inkjet press Óce Arizona 250® GT andconventional offset press KBA Performa 74). Film synthetic paper, offset prints and UV inkjet prints were artificiallyaged using standard techniques of accelerated ageing, such as moist-heat (80 °C and 65% relative humidity)and dry-heat (105 °C). Ageing was performed for periods of 1, 2, 3, 6 and 12 days. It was found that the moist-heataccelerated ageing influenced the most on optical properties of film synthetic paper. UV inkjet prints had highercolourfastness than the conventional offset prints. The most stable among all tested prints was the black colour UVinkjet print.